Legal and organizational aspects of the implementation of immunization in Poland after the COVID-19 pandemic - Kowalcze, Karolina; Wolnowska, Monika; Musiałowska, Karolina; Staśkiewicz, Wiktoria; Białek-Dratwa, Agnieszka; Krysiak, Robert; Stencel-Gabriel, Krystyna (Journal of Education, Health and Sport, 2022)
Introduction. Reducing the transmission of infectious diseases both among vaccinated individuals and the general population is only possible with the introduction of mandatory vaccination. The purpose of this article is to analyze the normative acts in force in the territory of the Republic of Poland, regulating mandatory and recommended immunizations. State of the art description. In Poland, immunization is mandatory and carried out in accordance with the Immunization Program for children and adolescents up to the age of 19, and persons particularly vulnerable to disease are published annually as a communiqué of the Chief Sanitary Inspector in the Official Journal of the Minister of Health. The issue of recommended immunizations is clarified by the Regulation of the Minister of Health of September 16, 2010, on the list of recommended immunizations and how to finance and document recommended immunizations required by international health regulations. According to Article 17(6) of the Law, vaccination may be performed by a doctor, feldsher, nurse, midwife, and school hygienist, as long as they have the appropriate qualifications. These qualifications are described in detail in the Ordinance of the Minister of Health of August 18, 2011, on mandatory immunization. According to Article 16 of the Law on Patient Rights and Patient Ombudsman, every patient has the right both to consent and to refuse certain health services. Conclusion. Immunization on the territory of the Republic of Poland is mandatory and is subject to legal regulation in the form of laws, regulations, and announcements, cited above. The exceptions are recommended vaccinations and COVID-19 vaccination, which are voluntary but are also legally normalized.